Building a quantum wireless network - O'Brien, DC; Schreir, A; Lee, V (IEEE, 2024)
Quantum Key Distribution (QKD) over optical fibres is a well-established area of research. Extending the reach of QKD using optical wireless links is less studied, however. This paper outlines some results from recent experiments, and methods to integrate wireless and wired QKD approaches.